2014
DOI: 10.1103/physrevb.90.235415
|View full text |Cite
|
Sign up to set email alerts
|

Conductance behavior in nanowires with spin-orbit interaction: A numerical study

Abstract: We consider electronic transport through semiconducting nanowires (W) with spin-orbit interaction (SOI), in a hybrid N-W-N setup where the wire is contacted by normal-metal leads (N). We investigate the conductance behavior of the system as a function of gate and bias voltage, magnetic field, wire length, temperature, and disorder. The transport calculations are performed numerically and are based on standard recursive Green's function techniques. In particular, we are interested in understanding if and how it… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 44 publications
3
72
1
Order By: Relevance
“…It is shown that the Dresselhaus SOC causes a gap for the triplet eigenmodes and, hence, an insuppressible spin relaxation. This contradicts the conjecture of previous authors [32][33][34]37,74,75] that Dresselhaus SOC is absent in 111 nanowires and, hence, cannot cause spin relaxation. Nevertheless, we found the lowest gap for the 111 growth direction which indicates a lower spin relaxation than for 001 or 110 nanowires.…”
Section: Discussioncontrasting
confidence: 86%
“…It is shown that the Dresselhaus SOC causes a gap for the triplet eigenmodes and, hence, an insuppressible spin relaxation. This contradicts the conjecture of previous authors [32][33][34]37,74,75] that Dresselhaus SOC is absent in 111 nanowires and, hence, cannot cause spin relaxation. Nevertheless, we found the lowest gap for the 111 growth direction which indicates a lower spin relaxation than for 001 or 110 nanowires.…”
Section: Discussioncontrasting
confidence: 86%
“…For higher values of the shift, the conductance is still suppressed in comparison to the quantized conductance 2G0 = 2e 2 /h. This suppression is caused by a mismatch of modes in the leads and in the wire, similarly to the one observed in Ref 44. for non-interacting systems.…”
supporting
confidence: 72%
“…As discussed in Ref. [64], the visibility of this helical gap depends on various factors which, importantly, include the actual value of the SO energy. Indeed, as the ratio μ lead /E SO is made larger, the visibility of the gap in G N is rapidly degraded (see lower curves in Fig.…”
Section: Normal Conductancementioning
confidence: 96%
“…For simplicity in the discussion, we model the gate-induced electrostatic potential with an abrupt profile (the role of smooth gate potentials has been recently discussed in Ref. [64]). …”
Section: Normal Conductancementioning
confidence: 99%